An experimental method to design piezoelectric energy harvesting skin using operating deflection shapes and its application for self-powered operation of a wireless sensor network. (June 2015) - Kim, Hongjin; Lee, Sowon; Cho, Chulmin; Kim, Jae Eun; Youn, Byeng Dong; Kim, Yoon Young
This work proposes a more practical way of designing the piezoelectric energy harvesting skin, which facilitates the application of the proposed idea to any practical engineering facilities with vibration. Unlike earlier studies to make use of analytical model for piezoelectric energy harvesting design, this work proposes an experimental method to design a piezoelectric energy harvesting skin using operating deflection shapes of a target mechanical system. This method is more practical in the sense that actual vibration of a target mechanical system can be characterized far better for the piezoelectric energy harvesting design. The key idea is to extract continuous in-plane normal strain values from discrete out-of-plane deformations of a target mechanical system. From multiple strain inflection lines, piezoelectric energy harvesting skin segments are designed to maximize a total power output. It is demonstrated that four piezoelectric energy harvesting skin segments designed by the proposed idea can generate sufficient power from the outdoor condensing unit of an air conditioning for self-powered operation of a wireless sensor network.